Fiber optical based parametric amplifier in a highly nonlinear fiber (HNLF) by using a ring configuration - Ahmad, Harith; Awang, Noor Azura; Harun, Sulaiman Wadi (Taylor & Francis, 2011)
A four-wave mixing (FWM) effect in a fiber-based optical parametric amplifier (FOPA) is reported. The novelty in the setup used is a ring cavity as opposed to the commonly used method of linear cavity. This reduces the required pump power, Pp, for the amplification of the signals and also the generation of the idlers. The achieved gain for signal amplification is about 30 dB with a Pp of 25 dBm. It has a flat gain response within range of 22 nm from 1570 nm to 1592 nm, with an average value of 28 dB within the 3 dB region. The average conversion efficiency is approximately -5 dB, with a peak value of -4 dB within the 2 dB region, with a range of 24 nm from 1576 nm to 1600 nm.